Interiority and Agency: Exploring Self in Context with Others in the Act of Creation - Young, Barbara (UI Scholars Hub, 2023)
This investigation seeks to extend the discourse on interiority. I am an interior designer and, therefore, pose questions as they relate to design process, specifically that the concern regarding interiority is not necessarily something to design for, but as designers, it affects how and what we design. The presented cases are artistic explorations that provided an opportunity to interrogate interiority as it relates to my cognitive and creative process. Through an auto-ethnographic account, I present two acts of making. In the creation process, I interrogate meaning-making and perception that constitutes my subjective interiority, which can only be understood in context. Using Maurice Merleau-Ponty to inform perception and Alfred Gell’s art nexus theory, derived from Peircean semiotics, I demonstrate how decisions, or judgements, are informed by my subjective interiority that has been formed by contextual experiences. Additionally, I argue that to understand interiority, we must move from perceived dichotomies such as interior and exterior, public and private, or individual and collective to viewing interiority and exteriority as continuous wholes.